Design of Pumping Stations Using a Multicriteria Analysis and the Application of the AHP Method - Sánchez-Ferrer, Diana S.; Briceño-León, Christian X.; Iglesias-Rey, Pedro L.; Martínez-Solano, F. Javier; Fuertes-Miquel, Vicente S. (Sustainability, 2021)
The pumping station is a very important hydraulic system in urban water supplies because the pumps raise the water head, ensuring the minimum pressure required in drinking water systems. In the design of a pumping station, one of the most important criteria is the number of pumps. However, in the traditional design, this criterion is defined arbitrarily. The other criteria are defined from the number of pumps and can produce a design that is not optimal. In addition, the traditional design does not consider the importance of the environment in choosing the pumps. The objective of this paper is to define a new design methodology for pumping stations. It has been developed using a multicriteria analysis in which nine criteria are evaluated. The application of the analytic hierarchy process (AHP) allows for finding an optimal solution. These design criteria have been associated in three cluster factors: technical factors; environmental factors; and economic factors. The results obtained allow us not only to validate the methodology but also to offer a solution to the problem of determining the most suitable model and the number of pumps for a pumping station.